FIRST RECORD OF Conotrachelus humeropictus FIEDLER, 1940 (COLEOPTERA: CURCULIONIDAE) IN THE STATE OF AMAPÁ, BRAZIL - Adaime, Ricardo (2020)
In this work we report for the first time in the state of Amapá, Brazil, Conotrachelus humeropictus Fiedler, 1940 (Coleoptera: Curculionidae) infesting fruits of Theobroma grandiflorum (Willd. ex Spreng.) K. Schum.Keywords: Curculionoidea; Theobroma grandiflorum; Cupuaçu; Fruticultura; Malvaceae.